Genetic diversity in morphological characters and phenolic acids content resulting from an interspecific cross between eggplant, Solanum melongena, and its wild ancestor (S. incanum). (24th January 2013) - Prohens, J.; Whitaker, B.D.; Plazas, M.; Vilanova, S.; Hurtado, M.; Blasco, M.; Gramazio, P.; Stommel, J.R.
Abstract: Solanum incanum, the wild ancestor of eggplant, Solanum melongena, has been considered as a source of variation for high content of phenolic acid conjugates in breeding programmes aimed at improving the functional quality of eggplant. We have evaluated the morphological and phenolic acids content in an interspecific family including S. incanum (P1), S. melongena (P2), their interspecific hybrid (F1), progeny from the selfing of the F1 (F2) and the backcross of the F1 to P2 (BC1P2). Many morphological differences were found between parents, while the F1 was intermediate for most traits. However, F1 plants were taller and pricklier and presented higher fruit flesh browning than any of the parents. F2 and BC1P2 were morphologically highly variable and the results obtained suggest that a rapid recovery of the characteristic combination of S. melongena traits can be achieved in a few backcross generations. Segregation for prickliness was found to be compatible with simple genetic control, prickliness being dominant over non‐prickliness. A total of 16 phenolic acid conjugates were studied, of which chlorogenic acid (5‐ O ‐( E )‐caffeoylquinic acid) was the most common compound in all samples, averaging 77.8% of all hydroxycinnamic acid derivatives. Contents of total phenolic acid conjugates were much higher in S. incanum than in S. melongena fruit flesh, and no major differences were found in the profile of phenolic acids among parents. The interspecific hybrid (F1) was intermediate between the two parents in phenolic acids content. Non‐segregating generations presented considerable variation in phenolic acids content, but the range of variation was wider in segregating F2 and BC1P2 generations. Additive genetic effects were the most important in explaining the results obtained for the phenolic acids content. A number of BC1P2 plants presented a good combination of phenolic acids content and fruit weight or flesh browning. Overall, the results demonstrate that improvement of functional quality in S. melongena can be obtained using S. incanum as a donor of alleles for high phenolic acids content.